Received Signal Strength Indicator Node Localization Algorithm Based on Constraint Particle Swarm Optimization - Songhao Jia; Cai Yang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Because the RSSI value greatly changes, the direct use of RSSI value has more errors in the positioning process as the basis to calculate the position of anchor nodes. This paper proposes a RSSI node localization algorithm based on constraint particle swarm optimization (PSO-RSSI). In the algorithm, particle swarm optimization is used to select anchor nodes set which are near the unknown node. The algorithm takes an element in the set, and measure distance between it and the other elements in the set. Then, the maximum likelihood method is used to calculate the coordinates. According to the difference between the calculated coordinates and the actual coordinates of the anchor node, the obtain coordinate of unknown node is corrected. When all the elements in the set perform such operation, the statistical methods are used to determine the coordinates of the unknown node. The algorithm embodies all the reference points influence on positioning, corrects the error problem on a single reference node positioning in the past. The simulation results show that the effect of the PSO-RSSI algorithm is more excellent.